Kinetic Analysis of the Living Ring‐Opening Polymerisation of L‐Lactide with Tin(II) Initiators. Issue 34 (18th October 2013) - Wang, Lingfang; Bochmann, Manfred; Cannon, Roderick D.; Carpentier, Jean‐François; Roisnel, Thierry; Sarazin, Yann
Abstract: A general kinetic model to describe the initiation and monomer depletion phases of the metal‐catalysed living ring‐opening polymerisation (ROP) of cyclic esters is presented. The model allows the description of ROP reactions in terms of rates of initiation ( k i ) and propagation ( k p ) and is in principle applicable to all metal‐mediated ROP reactions. The model was validated by curve‐fitting of data obtained for the living ROP ofL ‐lactide catalysed by a variety of tin(II) catalysts. The catalyst was chosen from tin(II) diisopropoxide or from heteroleptic complexes of the type (LO x )Sn(OR), in which (LO x ) is an amino or aminoether phenolate ancillary ligand and OR is isopropoxide or O ‐ tert ‐butyl lactate. All tested catalysts promote the controlled, living polymerisation ofL ‐lactide. No initiation phase was discerned for any of the considered catalysts in polymerisations performed at 60 °C, whereas at 25 °C initiation is an order of magnitude slower than propagation and, therefore, the inclusion of k i is required for an accurate kinetic description. Tin diisopropoxide is polymeric in the solid state, but it is dimeric in toluene solution. [Sn(O i Pr)2 ]2 is an excellent example of an aggregated catalyst precursor and is catalytically more active than the heteroleptic (LO x )Sn(OR). As dissociation of the inactive dimer into a catalytically active monomeric complex is required, half‐order dependence on [metal] is to be expected and was indeed found. A method to estimate the related monomer–dimer equilibrium constant K D under polymerisation conditions is also provided. Abstract : A detailed kinetic treatment of the living ring‐opening polymerisation ofL ‐lactide is proposed. This model gives access to the initiation ( k i ) and the propagation rate constants ( k p ). The model has been illustrated by using a variety of tin(II) precatalysts, including a dimeric one, for which it is demonstrated that a partial kinetic order of 0.5 is to be expected.